1991
DOI: 10.1007/bf00187901
|View full text |Cite
|
Sign up to set email alerts
|

On the possible role of endogenous lectins in early animal development

Abstract: In this review I have tried to summarize the information available on the lectins of developing embryos. The emerging evidence indicates that during fertilization carbohydrate-binding proteins play a role in sperm adhesion and in the reorganization of the extracellular matrix of the fertilized egg. Results also indicate that in adult tissues lectins participate in cell recognition and adhesion, and that several galactose-binding lectins function as receptors for laminin and, in principle could also interact wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 179 publications
1
16
0
Order By: Relevance
“…The tissue preparation was adjusted to 0.6 g/ml protein, and 20 l was added to the assay tube. Five Rzl of a fresh 1:20 dilution of the supplied GDP-[' 4 C]fucose in doubledistilled water was added to give a concentration of 0.425 nM. For standard incubations, 8 Il of a 200 mM stock of phenylgalactoside acceptor was added.…”
Section: A(1-2)-fucosyltransferase Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The tissue preparation was adjusted to 0.6 g/ml protein, and 20 l was added to the assay tube. Five Rzl of a fresh 1:20 dilution of the supplied GDP-[' 4 C]fucose in doubledistilled water was added to give a concentration of 0.425 nM. For standard incubations, 8 Il of a 200 mM stock of phenylgalactoside acceptor was added.…”
Section: A(1-2)-fucosyltransferase Assaymentioning
confidence: 99%
“…Cell surface glycoconjugates have been found to have a role in many cell adhesion processes, for instance, attachment of viruses and bacteria [1,2]; sponge cell adhesion [3]; adhesion of cells in the amphibian and early mammalian embryo [4][5][6]; and sperm-egg interactions [7]. Most recently, considerable evidence has accumulated for the role of lectin-carbohydrate binding in the interactions of leukocytes, in particular to the vascular endothelium during lymphocyte homing and before extravasation at sites of inflammation [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…To complete a recognition system based on the sugar code (Gabius 2000), endogenous lectins to decipher and translate the glycan messages are present in mammalian tissues (Harrison and Chesterton 1980;Barondes 1981;Gabius 1987Gabius , 1997Sharon and Lis 1989;Yoshizaki 1990;Zalik 1991;Rüdiger et al 2000; for collection of recent reviews, see Gabius and Gabius 1997;Gabius and Sinowatz 1998). Histochemically, their presence can readily be visualized by carrier-immobilized carbohydrate ligands, complementing popular studies on glycan profiling with plant and/or invertebrate lectins (Gabius et al 1993;Danguy 1995;Kannan and Nair 1997;Danguy et al 1998;Gabius 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Sara Zalik et al published many studies 1979-1999 on galectins during early chick embryogenesis (78,83). In the later studies she reported interesting morphological disturbances from adding simple galectin inhibitors like thiodigalactoside or lactose (84,85).…”
Section: E Some Early Galectin-storiesmentioning
confidence: 99%